A computational fluid dynamics study on different solar chimney designs on solar radiation - mohamed ramon; Hagar Alm ElDin Mohamad; Mohamed Samadony (Journal of Engineering Research - Egypt)
The solar chimney power plant (SCPP) is a hopeful solution to produce electrical power from solar energy. In this paper, a 2D numerical study is presented to estimate the performance of the SCPPs while varying the collector angle, chimney diverging angle, variable solar radiation and ambient temperature and some geometrical designs. Numerical models run with solar load discrete ordinates (DO) and realizable k-ɛ turbulence models. System is defined by the collector height =50 mm, the chimney diameter =160 mm, the collector diameter =2750 mm and the chimney height =3000 mm. its investigated for each case the profile of magnitude velocity, air temperature, pressure, incident radiation and turbulence characteristics were presented. The effective choice of the best geometry is based on the maximum value of the air velocity inside the SCPP. Results indicates that a negative collector-roof positively increases the air velocity, and the output power. To a specific limit, increasing the diverging angle of the chimney has a god effect on the velocity magnitude and the other parameters. also Increasing the collector diameter and chimney height and diameter has a great effect on power output as shown in results.